1995
DOI: 10.1172/jci118324
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variation in the promoter of the human apo CIII gene abolishes regulation by insulin and may contribute to hypertriglyceridemia.

Abstract: Overexpression of plasma apolipoprotein CIII (apo CIII) causes hypertriglyceridemia in transgenic mice. A genetically variant form of the human apo CIII promoter, containing five single base pair changes, has been shown to be associated with severe hypertriglyceridemia in a patient population. In animals and in cultured cells the apo CIII gene is transcriptionally downregulated by insulin. In this study we demonstrate that, unlike the wild-type promoter, the variant promoter was defective in its response to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
203
2
6

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(215 citation statements)
references
References 26 publications
4
203
2
6
Order By: Relevance
“…This major action of the hormone is important for normal metabolism but gains added significance in view of the fact that insulin resistance is the cornerstone of genetic diseases such as noninsulin-dependent diabetes mellitus and obesity. The possibility that faulty regulation of gene expression by insulin could result in disease is now given credence by the observations reported by Li et al (2) in this issue of The Journal.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…This major action of the hormone is important for normal metabolism but gains added significance in view of the fact that insulin resistance is the cornerstone of genetic diseases such as noninsulin-dependent diabetes mellitus and obesity. The possibility that faulty regulation of gene expression by insulin could result in disease is now given credence by the observations reported by Li et al (2) in this issue of The Journal.…”
mentioning
confidence: 80%
“…Recently, Dammerman et al (3) identified five polymorphisms in this region of the apo CIII promoter. Li et al (2) now show that single base pair changes at either of two of the five variant sites (at -482 and -455) abolish the repression of apo CIII gene transcription by insulin, an observation that reveals why these mutations lead to apo CIII overexpression. The functional significance of the nucleotide changes in the other three variant sites is unclear but is not related to regulation of apo CIII gene expression by insulin.…”
mentioning
confidence: 94%
“…In vitro studies showed that the simultaneous presence of the rare alleles of APOC3 C-482T and T-455C SNPs located in the IRE results in the up-regulation of the APOC3 gene in transfected HepG2 cells and could induce the over-expression of plasma apoCIII and the development of HTG (Li et al 1995). However, an association study between the presence of two APOC3 SNPs haplotypes, such as the T-482 and G3238 alleles, and HTG did not strengthen the association observed solely between the G3238 allele and HTG (Shoulders et al 1996;Surguchov et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the S2 allele, identified by the restriction enzyme Sst-I, is in disequilibrium with two mutations located in the promoter region of the apo C-III gene [9]. The presence of these two mutations determines the absence of regulation by the insu- lin and the decrease of apo-CIII, which is physiologically produced by the hormone, resulting in an increase in plasma concentrations of apoprotein CIII [19]. Apo C-III modulates the metabolism of triglyceride rich particles [20], so its overexpression could interfere in the plasmatic clearance of the triglyceride rich lipoproteins, resulting in its subsequent increase.…”
Section: Discussionmentioning
confidence: 99%